1997
DOI: 10.1093/ajcn/66.3.546
|View full text |Cite
|
Sign up to set email alerts
|

Hypoenergetic nutrition support in hospitalized obese patients: a simplified method for clinical application

Abstract: Nutrition support in obese hospitalized patients is controversial, with some practitioners advocating restricted energy or hypoenergetic feedings when patients are being actively treated for another disease. To eliminate the need for indirect calorimetry, this randomized, double-blind, prospective study was undertaken to determine whether obese hospitalized patients given a hypoenergetic parenteral regimen administered to provide 2 g protein x kg ideal body wt (IBW)(-1) x d(-1), could achieve nitrogen balance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
139
0
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(150 citation statements)
references
References 10 publications
1
139
0
10
Order By: Relevance
“…Insulin resistance, glucose intolerance, hyperlipidemia, nonalcoholic fatty liver disease, and hypoventilation syndrome are more prevalent in patients with obesity than nonobese patients. 59 As a result, the hospitalized patient with obesity is susceptible to experiencing complications associated with overfeeding. Because of these concerns, hypocaloric, high protein regimens have been designed by clinicians in an effort to minimize potential overfeeding complications while simultaneously achieving net protein anabolism.…”
Section: Accuracymentioning
confidence: 99%
See 3 more Smart Citations
“…Insulin resistance, glucose intolerance, hyperlipidemia, nonalcoholic fatty liver disease, and hypoventilation syndrome are more prevalent in patients with obesity than nonobese patients. 59 As a result, the hospitalized patient with obesity is susceptible to experiencing complications associated with overfeeding. Because of these concerns, hypocaloric, high protein regimens have been designed by clinicians in an effort to minimize potential overfeeding complications while simultaneously achieving net protein anabolism.…”
Section: Accuracymentioning
confidence: 99%
“…Four comparative studies [59][60][61][62] and 2 case series 63,64 examined the use of hypocaloric, high protein nutrition therapy for hospitalized patients with obesity. The hypocaloric, high protein diets contained average intakes ranging from 90 g to 140 g of protein and 900 kcals to 1300 kcals daily (Table 4).…”
Section: Accuracymentioning
confidence: 99%
See 2 more Smart Citations
“…Choban et al 55 demonstrated better glucose control with lesser need for exogenous insulin, but with no difference in mortality between the 2 groups. Overall, the average total caloric intakes in those studies ranged from 11 to 14 total kcal/kg ABW per day or 22 to 25 total kcal/kg IBW per day.…”
Section: Pnmentioning
confidence: 95%